The NF-κB Inhibitor, IMD-0354, Affects Immune Gene Expression, Bacterial Microbiota and Trypanosoma cruzi Infection in Rhodnius prolixus Midgut - Vieira, Cecilia S.; Moreira, Otacílio C.; Batista, Kate K. S.; Ratcliffe, Norman A.; Castro, Daniele P.; Azambuja, Patrícia (Frontiers in Physiology, 2018)
Rhodnius prolixus is an insect vector of Trypanosoma cruzi, the causative agent of Chagas disease in Latin America. Nuclear factor-κB (NF-κB) transcription factors (TF) are conserved components of the innate immune system in several multicellular organisms including insects. The drug IMD-0354 (N-(3,5-bis-trifluoromethyl-phenyl)-5-chloro-2-hydroxy-benzamide) is a highly specific inhibitor of IκB kinases. It blocks IκBα phosphorylation thus preventing nuclear translocation of the NF-κb TF. In humans, NF-κB is involved in several biological processes such as inflammation, cell proliferation and immunity. In insects, the activation of the immune system upon microbial challenge can be controlled by signaling pathways such as the immune deficiency (IMD) and Toll, to combat infection. These activated pathways signal to downstream NF-κB TF to stimulate specific immune genes, triggering the synthesis of several molecules such as the antimicrobial peptides. In Drosophila melanogaster, the activation and regulation of NF-κB TF have been elucidate, while in triatomines these mechanisms are not fully understood Therefore, the present study investigated the effects of oral administration of the drug IMD-0354 on the R. prolixus immune response to challenge with bacteria and T. cruzi, as well as the impact on the gut bacterial microbiota. R. prolixus were fed with rabbit blood containing IMD-0354 (Sigma-Aldrich) and Escherichia coli, Staphylococcus aureus or T. cruzi. The effects of IMD-0354 on insect mortality and antimicrobial activity in insect midgut samples, as well as the relative expression of R. prolixus immune genes were recorded. The bacterial microbiota was analyzed, and viable parasites were counted in insect midgut samples. The IMD-0354 treatment modulated antibacterial activity and the gene expression patterns of defensin A, defensin B, defensin C, and prolixicin, and the genes involved in the IMD and Toll pathways. Additionally, there was an increase of bacterial microbiota in treated insects. Insects treated with IMD-0354 and concomitantly infected with bacteria or T. cruzi through the blood meal had increased mortalities, while the T. cruzi population in R. prolixus midgut was reduced. The inhibitory effect of IMD-0354 indicates the importance of NF-κB TF in the innate immune responses involved in the control of bacteria and parasite infections in the R. prolixus midgut.